2020
DOI: 10.3390/atmos11080819
|View full text |Cite
|
Sign up to set email alerts
|

Changes Detected in Five Bioclimatic Indices in Large Romanian Cities over the Period 1961–2016

Abstract: Bioclimatic indices are very important tools to evaluate the thermal stress of the human body. The aims of this study were to analyze the general bioclimatic conditions in ten big cities in Romania and to find out if there has been any change in five bioclimatic indices over a 56‑year period: 1961–2016. The indices considered were: equivalent temperature, effective temperature, cooling power, universal thermal climate index and temperature-humidity index. They were calculated based on the daily meteorological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…The results of Banc et al . (2020) are consistent with the results of the present study. In fact, in low‐lying areas, there is an ascending trend in hot conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The results of Banc et al . (2020) are consistent with the results of the present study. In fact, in low‐lying areas, there is an ascending trend in hot conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Increasing trends for heat stress were also noticed in the southern part of Germany, where the frequency of days with a UTCI higher than 32 • C increased by about 50% [57]. A rising tendency of heat stress categories was also observed in some regions of Romania [80,81]. In the case of the mountains of the Polish-Saxon border area, the research confirmed that strong or very strong heat stress categories appear only in the lower hypsometric zones, while the summits are free from their occurrence [61,78].…”
Section: Discussionmentioning
confidence: 70%
“…A second level is that of scientific research. Climate warming in Romania (with changes in the patterns of severe atmospheric phenomena) is a reality confirmed by numerous local studies (Mihaila and Tanasa, 2005; Briciu, 2017), regional (Croitoru and Piticari, 2012;Mihaila and Briciu, 2012;Ontel and Vladut, 2015;Micu et al, 2017), national (Croitoru et al, 2012;Croitoru et al, 2016;Banc et al, 2020) and in Central and Eastern Europe (Luterbacher et al, 2004). These studies directly relate atmospheric heating to the parameters of meteorological-climatic risk phenomenology.…”
Section: Introductionmentioning
confidence: 90%